Infrared spectroscopy of serum fails to identify early biomarker changes in an equine model of traumatic osteoarthritis. Issue 4 (December 2022) - Panizzi, L.; Vignes, M.; Dittmer, K.E.; Waterland, M.R.; Rogers, C.W.; Sano, H.; McIlwraith, C.W.; Pemberton, S.; Owen, M.; Riley, C.B.
Abstract: Objective: to determine the accuracy of infrared (IR)-based serum biomarker profiling to differentiate horses with early inflammatory changes associated with a traumatically induced model of equine carpal osteoarthritis (OA) from controls. Method: unilateral carpal OA was induced in 9 of 17 healthy Thoroughbred fillies, while the remainder served as sham operated controls. Serum samples were obtained before induction of OA (Day 0) and weekly thereafter until Day 63 from both groups. Films of dried serum were created, and IR absorbance spectra acquired. Following pre-processing, partial least squares discriminant analysis (PLSDA) and principal component analysis (PCA) were used to assess group and time differences and generate predictive models for wavenumber ranges 1300-1800 ​cm −1 and 2600-3700 ​cm −1 . Results: the overall correct classification rate when classifying samples by group (OA or Sham) was 52.7% (s.d. ​= ​12.8%), while it was 94.0% (s.d. ​= ​1.4%) by sampling Day. The correct classification results by group-sampling Day combinations with pre-intervention serum (Day 0) was 50.5% (s.d. ​= ​21.7%). Conclusion: with the current approach IR spectroscopic analysis could not differentiate serum of horses with induced carpal OA from that of controls. The high classification rate obtained by Day of sampling may reflect the effect of exercise on the biomarker profile. A longer study period (advanced disease) or naturally occurring disease may provide further information on the suitability of this technique in horses.